2013
DOI: 10.1371/journal.pone.0064766
|View full text |Cite
|
Sign up to set email alerts
|

Fusing a Carbohydrate-Binding Module into the Aspergillus usamii β-Mannanase to Improve Its Thermostability and Cellulose-Binding Capacity by In Silico Design

Abstract: The AuMan5A, an acidophilic glycoside hydrolase (GH) family 5 β-mannanase derived from Aspergillus usamii YL-01-78, consists of an only catalytic domain (CD). To perfect enzymatic properties of the AuMan5A, a family 1 carbohydrate-binding module (CBM) of the Trichoderma reesei cellobiohydrolase I (TrCBH I), having the lowest binding free energy with cellobiose, was selected by in silico design, and fused into its C-terminus forming a fusion β-mannanase, designated as AuMan5A-CBM. Then, its encoding gene, Auman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 26 publications
(30 reference statements)
0
22
0
Order By: Relevance
“…Interestingly, GusA-CBD exhibited maximal activity at higher temperatures and acidic pH levels compared to free GusA. In a previous study, a family I carbohydrate-binding module of Trichoderma reesei cellobiohydrolase was fused with β-mannanase, resulting in an optimal temperature that was 5–8°C higher than that of free β-mannanase [13]. These results indicate that GusA-CBD is relatively stable at higher temperatures and more acidic pH values than free enzyme.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Interestingly, GusA-CBD exhibited maximal activity at higher temperatures and acidic pH levels compared to free GusA. In a previous study, a family I carbohydrate-binding module of Trichoderma reesei cellobiohydrolase was fused with β-mannanase, resulting in an optimal temperature that was 5–8°C higher than that of free β-mannanase [13]. These results indicate that GusA-CBD is relatively stable at higher temperatures and more acidic pH values than free enzyme.…”
Section: Resultsmentioning
confidence: 81%
“…Additionally, constructing synthetic scaffolds using the CBD-based system may further improve the metabolite conversion rate by increasing local enzyme concentration and reducing intermediate loss caused by diffusion or side reactions [5]. For example, the fusion of various CBD molecules to the N- or C-termini of other enzymes may enhance enzyme catalytic efficiency by increasing their local concentrations around the polysaccharide substrates such as insoluble cellulose, and/or improve catalytic activity and thermostability [13,23]. …”
Section: Discussionmentioning
confidence: 99%
“…Binding of AnAXE and AnAXE-CtCBM3 to corncob xylan was examined by native affinity gel electrophoresis as described by Freelove et al [40]. Briefly, native polyacrylamide gels prepared for these analyses contained 7.5% (w/v) bis-acrylamide, 25 mM Tris/250 mM glycine buffer (pH 8.6) and 0.01% (w/v) of corncob xylan.…”
Section: Affinity Gel Electrophoresismentioning
confidence: 99%
“…While published impacts of CBM addition on enzyme thermostability vary, earlier studies demonstrate the potential of CBMs from thermophilic organisms to increase the thermostability of appended catalytic domains [40,41]. Accordingly, to evaluate the effect of the CtCBM3 module on AnAXE stability, the half-life of AnAXE at 60 • C was used to as a baseline to study impacts of the CtCBM3 fusion.…”
Section: Ph Optimum and Temperature Stabilitymentioning
confidence: 99%
“…Several studies have shown that the fusion of CBMs into other enzymes can improve the catalytic activity or the substrate affinity. For example, fusion enzyme was constructed by fusing CBM to the C‐terminus region of β‐mannanase, resulting in an obvious decrease in Km and a slight alteration in Vmax . Chen et al fused the CBM from Alkalimonas amylolytica α‐amylase (CBM A my) to cyclodextrin glycosyltransferase from Paenibacillus macerans to improve 2‐O‐D‐glucopyranosyl‐L‐ascorbicacid (AA‐2G) productivity .…”
Section: Introductionmentioning
confidence: 99%